(untitled) (Research, Society and Development, 2020)
Objective: To report the experience of nursing students in a Basic Health Unit (UBS) in the capital of Amazonas through the action plan on pathologies caused by stress at work. Method: this is an experience report in a BHU in the city of Manaus, whose tool used in the planning, intervention and evaluation of actions was the 6W3H instrument. Results: the importance of caring for the person in his / her vulnerability was evidenced with a view to the renewal of this individual within society with the preservation of psychological, emotional, social and occupational health. Conclusion: At the end of the work, a relevant contribution to the academic life was identified, as well as the stress factor as the cause of the illness of the being who works with his / her emotional affected, needing a holistic interventionist assistance. In addition, it was allowed to work with data consistent in loco that contemplated the importance of the mental health of the worker who shares life in society.